Titanium Dioxide (TiO2) Doping Copper (Cu) with Annealing Temperature Variation as Photoanode for Dye-Sensitized Solar Cells (DSSC) - Hasna Ainun Nuurul Ma'rifah Enna; Supriyanto Agus; Paramitha Tika; Widiyandari Hendri; Purwanto Agus; Kasuma Kiwi Aliwarga Harry (E3S Web of Conferences, 2023)
Cu-doped Titanium Dioxide (TiO2) has been widely used as a DSSC photoanode material. The annealing temperature affects the structural analysis and optical properties of DSSC photoanodes. Structural analysis showed that the crystal size increased with increasing annealing temperature. The XRD results showed that the sample formed an anatase phase at annealing temperatures of 300℃ and 400℃, while at 450℃ and 500℃ there was an anatase-rutile mixed phase. The results of SEM morphology data obtained average particle diameters for CT300, CT400, CT450, and CT500 materials were 23.87 μm, 32.54 μm, 33.38 μm, and 37.63 μm respectively. UV-Vis testing shows absorbance in the ultraviolet region at 350-400 nm. Increasing the annealing temperature decreases the absorbance. The efficiency of DSSC compared to undoped materials is 0.44% to 0.71% in samples with an annealing temperature of 300℃ which is the sample with the highest efficiency. The efficiency value decreased with increasing annealing temperature.